Formação de intelectuais negros e negras : a experiência de assessores/as educacionais para assuntos da comunidade negra no estado de São Paulo - Souza, Erivelto Santiago (2009)
The present research - Formation of black intellectualls: the experience of educational Advisors to the Black comunnity issues in the State of São Paulo was conducted under the Line Search Social Practices and Educational Processes that is part of Post-Graduate Program in Education at Universidade Federal de São Carlos (PPGE/UFSCar); under the Research Group Social Practices and Educational Processes ; and under Center for Studies Afro-Brazilian (NEAB/UFSCar). The research aims to describe and understand educational processes in social practice to combat racism experienced by Advisors to the Black comunnity issues who were forming themselves as black intellectuals when they performed their duties with the Department of Education in the State of São Paulo in 80´s. The research is anchored in the study of education and ethnic-racial relations in Brazil, as well as theoretical references of the Line Search "Social Practices and Educational Processes". The key concepts of this study are Social Practices in the Educational Process; Black Movement and Education; Tackling racism in education. The deepening of the theoretical concepts are given from studies of Pedagogy and Philosophy of Liberation, particularly those submitted by Paulo Freire and Enrique Dussel. The theory was further from the studies of social movements from the perspective of Alain Touraine and Maria da Glória Gohn; combat racism in education from the studies of Petronilha Beatriz Gonçalves e Silva and Luiz Alberto Oliveira Gonçalves, which takes the debate on intellectual black. The research investigated the action of the Working Group for Afro-Brazilian Affairs (GTAAB) who worked with the Department of Education of the State of São Paulo between the years 1986 and 1989, and developed policies and educational projects to combat racism. Seeking reveal the processes of formation of Advisors as intellectuals, we chose a position based on Phenomenology. As methodological procedures, the researcher was used to consult the documents, conversations and semi-structured interviews with participants in the research. Interviews were conducted with five persons: four of them were part of the GTAAB and one of them did not participate directly, but has closely followed the activities of this Group. Data analysis indicates an action of the Advisors educational: at the moment that they develop its activities with the Department of Education of the State of São Paulo, they sought articulate knowledge offered by their areas of training with those offered by participation in civil society groups, particularly those dedicated to ethnic-racial issue. To do that, they took positions which may be expressed thus: write together, teach and learn from each other, learn from the adversity, being together and doing together.